A narrativa do câncer nas telenovelas - Santana, Dhione Oliveira (2021)
No other work of audiovisual fiction in the Brazil has managed to arouse the interest of the Brazilian public as much as soap operas. Having its origin linked to the literature of French novels in the nineteenth century, here, the genre became “Brazilianized”, adopting its own aesthetics and themes that approach the daily life of the Brazilian public, with emphasis on issues of social relevance involving health and illness. It is not uncommon for these products, through social merchandising, to address topics such as cancer, a disease that will affect 625,000 Brazilians for each year of the 2020- 2022 triennium. Since telenovelas address this health condition, our objective was, through the content analysis of the 9 pm telenovelas on Rede Globo de television, to understand how it is portrayed. In the study, we coded seven categories that described: 1. "Character Profile", 2. "Types of Cancer", 3. "Causes of Cancer", 4. "Cancer Findings and Symptoms", 5. "Submitted Treatments", 6. “Cancer Stage and Disease Outcome”, 7. “Dramatic Reasons”. We note that most of the characters who had the disease are adult women, from upper-middle social class, with the most varied tumors (seven types in all), without clear medical causes for the disease, with treatments that follow the recommendations of the medical literature specific, but with a high fatality rate. The high lethality of the characters was justified, from a fictional point of view, by the need to explore the suffering of the good guys, as punishment for cruel acts, a reason for their change in their moral conduct, as well as a dramatic resource that allowed changes in the directions of the analyzed narratives.